Сучасні біографічні та генеалогічні дослідження: шляхи зближення та трансформації - Лобко, Н.В. (Українська біографістика, 2010)
Сompares subject, object, goal and sources of genealogical and bibliographic studies. On the analysis of changes in the historical-bibliographic and historicalgeneological research the author came to the conclusion about their convergence in the united historical-geneological-biographical studies.